Implementation of National Defense Values Through Student Character Strengthening Program at SMP Unismuh Makassar - Mustaring; Mustari; Muhajira Nurul Lutfiya; Najamuddin (Pustaka Digital Indonesia, 2024)
This research aims to: 1). Analyzing the forms of activities in the character strengthening program for students at the junior secondary education level. 2. Analysis of the implementation of state defense values in students involves understanding and evaluating the efforts and activities carried out by schools to integrate and instill state defense values in students. The values of defending the country include love of the country, discipline, independence, responsibility and tolerance. This type of research uses qualitative research. The methods and data sources used to analyze the implementation of state defense values are documentation, interviews, field research and official documents from schools. The research results show that: 1). The form of activity for the Student Character Strengthening Program at Unismuh Makassar Middle School makes a positive contribution to the formation of student character. By organizing various activities that prioritize the development of personality values, this program is able to provide a holistic experience for students. The existence of extracurricular activities, character building, LDKS, and social activities can help improve the quality of students' character at Makassar Unismuh Middle School. 2). The implementation of national defense values at Unismuh Makassar Middle School provides a strong foundation in forming students' sense of love for their country and social awareness. Involving students in activities that foster a spirit of patriotism and leadership, this implementation has great potential to create a generation with high integrity and readiness to face the nation's challenges.